Estimation of the mean lactation curve in crossbred female buffaloes (Buffalypso x Carabao) - Garc?a, Yenny; Fraga, Luis Mateo; Guzm?n, Gladys; Mora, Marta; Garc?a, Dayron; Padr?n, E. (Cuban Journal of Agricultural Science, 2013)
The mean lactation curve of crossbred female buffaloes (Buffalypso x Carabao) was characterized in the Genetic Cattle Enterprise ?El Cangre?. A total of 18 412 productions of the control day (PCD) out of 1 377 female buffaloes were used. The minimum square constants of the PCD were obtained with the Mixed procedure of the SAS. The hyperbolic, square logarithmic, incomplete gamma, Wilmink, linearsquare segmented polynomial, square-square segmented polynomial um linear function and polynomial with three square segments were used for adjusting the curve through the NLIN of SAS. When selecting the best model, the determination coefficient, adjusted determination coefficient, estimation standard error, model signification test, the test of Durbin Watson, the test of ?Lack of Fit?, distribution of the residues and deviation between the total observed and estimated milk productions were considered. The means of the PCD were between 2.15 ? 0.04 kg and 4.19 ? 0.03 kg. The lactation peak occurred in the second month with production of 4.03 kg. The goodness of fit and discrimination between the models demonstrated high fit in the square logarithmic model and polynomials, with two and three square segments. However, the polynomial with three square segments (Y=3.5281+ 0.6903X -0.1791X2+ 0.1818Z1+0.0922Z2) had significant parameters with the highest fit values and estimated with precision all the phases of the curve. It is considered that this model represented the best the mean lactation curve of the female buffaloes under the conditions of the enterprise. Key words: curve, lactation, crossbred female buffaloes.